"Evaluación del potencial de la cascarilla de café como combustible para la reducción de óxidos de nitrógeno (NOx) en la combustión de carbón bituminoso, bajo los procesos de co-combustión (co-firing) y requemado (reburn)" (2017)
The main objective of this project is to measure the decrease of the combustion output of NOx emissions using the method of Cofiring and Reburn with coal and biomass (Coffee Husk). More specifically, obtain the thermal and chemical characteristics of coal and biomass including the proximate and ultimate analyses. We graphed the temperature profile as a function of the chambers distance for both combustion process. In addition, we graphed the NOx emissions as function of the weight percentage of the biomass for the Cofiring process, and the NOX emissions as function of the injection distance of biomass for the Reburn process.